Physical-recreational activities: an option to favor the social integration of young alcoholics - Albert Noa-Pérez; María Adela Ceballos-Rubio (Universidad de Guantánamo, 2013)
The work provides a tool for the teacher of Physical Culture, where the system of physical and recreational activities developed aims to promote the social integration of young alcoholics laundry community, municipality Maisí, the same methods were used empirical and theoretical level that allowed diagnose the current situation of the subject investigated and verify the feasibility of the proposal. In general it is considered that the results are satisfactory and correspond to the interests of resolving a current problem for the process of recreational sports in the community studied.